2015
DOI: 10.1146/annurev-arplant-043014-114720
|View full text |Cite
|
Sign up to set email alerts
|

Moving Toward a Comprehensive Map of Central Plant Metabolism

Abstract: Decades of intensive study have led to the discovery of the main pathways involved in central metabolism but only some of the pathways and regulatory networks in which they are embedded. In this review, we discuss techniques used to assemble these pathways into a systems biology framework that can enable accurate modeling of the response of central metabolism to changes, including ways to perturb metabolic systems and assemble the resulting data into a meaningful network. Critically, these networks are of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 152 publications
(182 reference statements)
0
21
0
Order By: Relevance
“…In addition, recent research has revealed that the extents of qualitative and quantitative variation of metabolism within a species are much larger than had previously been assumed [6]. Plant metabolites play vital roles in growth, cellular replenishment, and whole-plant resource allocation, as well as in adaptation of plants to a constantly changing environment [7,8]. Hence, the metabolome is consequently often regarded as the 'readout' of the physiological status and the bridge between the genotype and the phenotype of a plant [9][10][11].…”
Section: Simple Beginning: the Significance Of Plant Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent research has revealed that the extents of qualitative and quantitative variation of metabolism within a species are much larger than had previously been assumed [6]. Plant metabolites play vital roles in growth, cellular replenishment, and whole-plant resource allocation, as well as in adaptation of plants to a constantly changing environment [7,8]. Hence, the metabolome is consequently often regarded as the 'readout' of the physiological status and the bridge between the genotype and the phenotype of a plant [9][10][11].…”
Section: Simple Beginning: the Significance Of Plant Metabolismmentioning
confidence: 99%
“…The Diversity of Plant Metabolism Although most primary metabolites constitutively accumulate in plant cells [8], the majority of specialized metabolites are only detected in defined species, within particular tissues/organs, Plants produce a huge array of metabolites in spatiotemporal-and/or environment-dependent manner, which not only make it a challenge to understand plant metabolic diversity but also render plants ideal models for identifying metabolites and dissecting metabolic pathways.…”
Section: Genetic and Biochemical Insights Into Plant Metabolismmentioning
confidence: 99%
“…Plant metabolism can be divided into two general categories: primary and specialized metabolism [6]. Primary metabolism involves compounds critical to growth, development and reproduction of the plant, whereas specialized metabolism encompasses compounds needed for the plant to successfully cope with abiotic and biotic stresses ( Figure 1) [5][6][7]. These classes of metabolism are intrinsically linked; the metabolites of primary metabolic pathways, such as glycolysis, the pentose-phosphate pathway, and the tricarboxylic acid cycle, also serve as building blocks for secondary metabolic pathways.…”
Section: Plant Metabolism Is a Complex And Dynamic Processmentioning
confidence: 99%
“…From the ancient valleys of Mesopotamia to the Amazonian rainforests, plants have served as sources to provide humans with metabolites for food and nutrition, biomaterials for living, and treatment for pain and disease (Wurtzel and Kutchan, ). Plants also evolved the biosynthesis of numerous compounds with vital roles in growth, cellular replenishment, and whole‐plant resource allocation, as well as in their adaptation to a constantly changing environment (Obata and Fernie, ; Sulpice and McKeown, ).…”
Section: Introductionmentioning
confidence: 99%